Singer tops season lineup (Raton, NM Raton Range, 1996)
Article is about the Arts Council's season lineup starting with the singer Michael Martin Murphy.
Newspaper article
Master list item #: 103
File location is in the Raton file Cabinet
Keywords: Murphy, Michael Martin -- Musician; New Mexico Symphony -- Musical group; Kim and Reggie Harris -- Musical Group; Doge City Cowboy Brass Band; Play 'Pocahontas'; Live Performance; Performance Lineup; Season Promotion; Music Performance; Shuler Theater; Raton, New Mexico